Efficient data retrieval algorithms for multiple requests in MIMO wireless networks. (22nd December 2014) - He, Ping; Shen, Hong; Guo, Longkun; Li, Yidong
Summary: Given a set of multiple channels, a set of multiple requests, where each request contains multiple requested data items and a client equipped with multiple antennae, the multi‐antenna‐based multirequest data retrieval problem (DRMR‐MA) is to find a data retrieval sequence for downloading all data items of the requests allocated to each antenna, such that the maximum access latency of all antennae is minimized. Most existing approaches for the data retrieval problem focus on either single antenna or single request and are hence not directly applicable to DRMR‐MA for retrieving multiple requests. This paper proposes two data retrieval algorithms that adopt two different grouping schemes to solve DRMR‐MA so that the requests can be suitably allocated to each antenna. To find the data retrieval sequence of each request efficiently, we present a data retrieval scheme that converts a wireless data broadcast system to a special tree. Experimental results show that the proposed scheme is more efficient than other existing schemes. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Multi‐antenna‐based multirequest data retrieval problem (DRMR‐MA) is to find a data retrieval sequence for downloading all data items of the requests allocated to each antenna, such that the maximum access latency of all antennae, is minimized. This paper proposes two data retrieval algorithms that adopt two different grouping schemes to solve DRMR‐MA. And we present a data retrieval scheme that converts a wireless data broadcast system to a special tree for finding the data retrieval sequence of each request.